The Visible Characteristic of Modified Cassava Flour-Noodle after Treatment with Mineral Salt. Issue 1 (1st May 2022) - Al-Baarri, A N; Widayat; Legowo, A M; Mawarid, A A; Dewanti, A; Zain, N D J; Rohma, Z A; Lestari, F P; Pangestika, W
Abstract: Noodles are made from the main ingredient of wheat flour obtained through imports. In order to reduce imports of wheat flour, modified cassava flour or mocaf can be used as wheat replacement. Mocaf is flour made from cassava through a fermentation process. Due to the fermentation process, mocaf has characteristics similar to wheat flour but does not contain gluten and low in protein, so that the texture of the noodles made of mocaf is less firm, brittle, and much brighter. One alternative that can be done to improve and maintain the texture, color and salinity of noodles made from mocaf is to add mineral salt. Therefore, this research was conducted to improve the color and determine the salinity of noodles made from mocaf with the addition of the salt. Noodles with wheat flour (C), wheat flour and mocaf (MF), mocaf with mineral salt (MFM). Based on the results of the study, significant changes were detected in MFM noodles. The color of MFM noodles showed brighter than C and MF noodles. In conclusion, the addition of mineral salt to mocaf noodles could increase brightness and salinity.